Empowerment Of The Community Through Integrated Coaching Post For Non-Communicable Disease - Ni Wayan Suniyadewi; Nurul Faidah; Ni Komang Sukraandini (Perkumpulan Peneliti Ilmu Lingkungan - Green Visioneers, 2019)
The prevalence of Non-Communicable Diseases in Indonesia has increased. According to the Bali Province Riskesdas (2013) people who are obese 15.2%, Diabetes Mellitus (DM) by 1.4%, hypertension 5.3% based on the interview method and 18.4% through measurement, on average increase at the age of 45 years and over by 0.4%. One of the Puskesmas in Denpasar City is Puskesmas III North Denpasar. On average, the target area experiences a lifestyle transition from rural to urban. The community began to switch from farm work to office workers so that the time and activity of their movements were very limited. Hypertension, diabetes mellitus and rheumatism are diseases that are always present in a series of 10 major diseases based on a visit to the Puskesmas III North Denpasar (Register of Health Center III North Denpasar, 2017). Based on the above phenomenon, it is very necessary to form a forum as a center for health services in order to improve the health status of the people especially those aged 15 years and over. Interviews with the head of Puskesmas III North Denpasar strongly support the establishment of integrated coaching post for non-communicable diseases which is expected to be a primary health care center for the promotion and prevention of disease.